2013
DOI: 10.3892/br.2013.153
|View full text |Cite
|
Sign up to set email alerts
|

Effects of apoptosis-related proteins caspase-3, Bax and Bcl-2 on cerebral ischemia rats

Abstract: Abstract. Neuron apoptosis is known to mediate a change of ethology following cerebral ischemia̸reperfusion injury in rats. Additionally, Bcl-2, Bax and caspase-3 proteins may exert a significant effect on neuron injury. The aim of this study was to investigate the role, mechanism of action and clinical significance of these proteins in neuron apoptosis and functional impairment following cerebral ischemia̸reperfusion injury in rats. Sixty male healthy adult Wistar rats were randomly assigned into control (n=6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
79
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(85 citation statements)
references
References 14 publications
6
79
0
Order By: Relevance
“…Moreover, the mRNA and protein expression levels of Caspase-3 and Bax could be reduced, whereas those of Bcl-2 could be increased after inhibition of the SOCS1-JAK2-STAT3 pathway. In conjunction with these studies, the activation of caspase-3 and Bax and the down-regulation of Bcl-2 have been reported to be strongly associated with neuron apoptosis, as Bax expression results in activated caspase-3 and indirectly inhibits Bcl-2 expression via the formation of Bax/Bcl-2 heterodimers, which initiate cell apoptosis following cerebral ischemia/reperfusion injury [28]. As an important signaling pathway, the JAK2/STAT3 pathway can regulate a variety of cell biological activities such as the immune response, cell differentiation and cell growth [29].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the mRNA and protein expression levels of Caspase-3 and Bax could be reduced, whereas those of Bcl-2 could be increased after inhibition of the SOCS1-JAK2-STAT3 pathway. In conjunction with these studies, the activation of caspase-3 and Bax and the down-regulation of Bcl-2 have been reported to be strongly associated with neuron apoptosis, as Bax expression results in activated caspase-3 and indirectly inhibits Bcl-2 expression via the formation of Bax/Bcl-2 heterodimers, which initiate cell apoptosis following cerebral ischemia/reperfusion injury [28]. As an important signaling pathway, the JAK2/STAT3 pathway can regulate a variety of cell biological activities such as the immune response, cell differentiation and cell growth [29].…”
Section: Discussionmentioning
confidence: 99%
“…Bcl-2 has been shown to function as a negative regulator of cellular apoptosis (27) and increasing evidence has implicated Bcl-2 in the regulation of autophagy (28,29). Bcl-2 was found to bind to Beclin1 and disrupt autophagy, and overexpression of Bcl-2 in the heart inhibited autophagy in response to starvation.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, MDA expression increased and SOD expression decreased in the HIBD group. Studies have shown that neuronal apoptosis in an ischemia-reperfusion injury model may be associated with Bax upregulation and Bcl-2 downregulation [25]. Increased Bcl-2 expression and decreased Bax expression have been shown to be involved in the inhibition of HIBD in the subventricular zone of rats [26].…”
Section: Discussionmentioning
confidence: 99%